Dialogue of epochs in music thinking of Arvo Pärt: “Credo” - Liva, Natalia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Relevance of the study. One of the most important functions of musicological research is to indicate those tendencies in music which define the mainstream of the epoch, reflect its pulse. The necessity of this capacity becomes more and more vital when it comes to the analysis of the problems of contemporary art. Getting over the period of atheism, return to spirituality and seeking for God is characteristic of the pro-European culture of the second half of the 20th century. The tendency is represented by respective essential topics of the art discourse that form music mentality. One of these most substantial aspects is the significance of Johann Sebastian Bach's works for a contemporary listener. According to this important tendency, the central attention in the article has been focused on one of the works of Arvo Pärt, the famous Estonian composer, for whom the phenomenon of Bach’s music is rather valuable. The author represents Bach theme in the shape of a dialogue of the past and the present. Main objective of the study is to accomplish a detailed analysis of different semantic levels of Arvo Pärt’s «Credo» (1968), written for a symphony orchestra, a mixed choir and a piano, so as to explain its close connection with the main cultural and music tendencies of the last half of the 20th century. Methodology. The key methodological instrument of the research proposed is hermeneutics. In this context a concept of the work, its genre indications and the peculiarities of musical language have been carefully examined. J. S. Bach’s 1st Prelude in ’c’ major from the first volume of «The well-tempered clavier», literally quoted in the «Credo» by the composer, has been analysed separately for the purpose to clarify the author's inner motivation of using it in the work. Results and conclusions. The accomplished study enables to derive the following conclusion: according to the results of the multi-level hermeneutic analysis, Arvo Pärt’s «Credo» should be classified as a typical and characteristic musical phenomenon of the last half of the 20thcentury.